2020
DOI: 10.1093/ptj/pzz127
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapist Clinical Practice Guideline for the Management of Individuals With Heart Failure

Abstract: The American Physical Therapy Association (APTA), in conjunction with the Cardiovascular and Pulmonary Section of APTA, have commissioned the development of this clinical practice guideline to assist physical therapists in their clinical decision making when managing patients with heart failure. Physical therapists treat patients with varying degrees of impairments and limitations in activity and participation associated with heart failure pathology across the continuum of care. This document will guide physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 143 publications
0
80
0
7
Order By: Relevance
“…If physical therapists recognize signs and symptoms of acute decompensation, such as S3 heart sound, pulmonary crackles, and increase in peripheral edema, it is crucial to recommend prompt medical follow-up. Utilization of the detailed algorithms provided in the article of Dias et al 2 can also be used as a supplement to the algorithms presented in the HF CPG given by Shoemaker et al 3 .…”
Section: Heart Failurementioning
confidence: 99%
“…If physical therapists recognize signs and symptoms of acute decompensation, such as S3 heart sound, pulmonary crackles, and increase in peripheral edema, it is crucial to recommend prompt medical follow-up. Utilization of the detailed algorithms provided in the article of Dias et al 2 can also be used as a supplement to the algorithms presented in the HF CPG given by Shoemaker et al 3 .…”
Section: Heart Failurementioning
confidence: 99%
“…Specific details of the guideline development methodology and literature review can be found in the full guideline published in the Physical Therapy journal. 4…”
Section: Guideline Development Methodologymentioning
confidence: 99%
“…NYHA classes I-IV represent patient symptoms that vary bidirectionally where there can be progression and regression of symptoms depending on a patient's current state. 4 Reprinted from Phys Ther. 2020; 100(1):14-43, with permission of the American Physical Therapy Association.…”
Section: Categories and Classification Of The Severity Of Heart Failurementioning
confidence: 99%
“…Оценка симптомов течения хронической сердечной недостаточности (ХСН), особенно на фоне таких заболеваний, как ревматоидный артрит (РА), сопровождающихся выраженным болевым синдромом и снижением качества жизни пациентов, важна для получения детальной и целостной картины заболевания. У пациентов с ХСН и РА такие первые неспецифические проявления ХСН, как повышенная утомляемость, снижение толерантности к физической нагрузке, спад повседневной активности, могут маскироваться под симптомы РА [1,2]. В свою очередь, снижение физической активности, по мнению ряда исследователей, может быть причиной увеличения риска развития декомпенсации ХСН, ввиду ухудшения кровообращения органов и тканей, в том числе миокарда [3,4].…”
Section: обоснованиеunclassified